2016
DOI: 10.1097/md.0000000000003154
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Blood Dose in Patients Treated With 131I Using MIRD, Imaging, and Blood Sampling Methods

Abstract: Radioiodine therapy is known as the most effective treatment of differentiated thyroid carcinoma (DTC) to ablate remnant thyroid tissue after surgery. In patients with DTC treated with radioiodine, internal radiation dosimetry of radioiodine is useful for radiation risk assessment. The aim of this study is to describe a method to estimate the absorbed dose to the blood using medical internal radiation dosimetry methods.In this study, 23 patients with DTC with different administrated activities, 3.7, 4.62, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Time spent in close proximity to the patient and potential for contaminated clinical waste must be considered; for some patients, extended stays in hospital may be required so that radiation doses and clinical waste can be controlled within a hospital environment under guidance of the RPA/RWA. For injections following discharge from RAI treatment, using estimates of radioactivity in the blood following RAI administration [39] it has been shown that the level of radioactivity in sharps waste is unlikely to exceed the 40 KBq limit and therefore such waste can be disposed of via typical clinical waste routes such as via the general practitioner surgery. Written guidance should be provided to patients on best practice for handling waste.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent in close proximity to the patient and potential for contaminated clinical waste must be considered; for some patients, extended stays in hospital may be required so that radiation doses and clinical waste can be controlled within a hospital environment under guidance of the RPA/RWA. For injections following discharge from RAI treatment, using estimates of radioactivity in the blood following RAI administration [39] it has been shown that the level of radioactivity in sharps waste is unlikely to exceed the 40 KBq limit and therefore such waste can be disposed of via typical clinical waste routes such as via the general practitioner surgery. Written guidance should be provided to patients on best practice for handling waste.…”
Section: Discussionmentioning
confidence: 99%
“…I-131 dosimetry should be calculated from a series of SPECT images generated time-activity curves. Therefore, the complicated operation process [21], imaging method [5] and calculation model may be limited in clinical application [22]. In this study, the actual activity of the therapeutic dose of I-131 in thyroid remnant tissue was quantified as %ID, and the operation process was performed by thyroid SPECT/CT scanning from whole-body iodine planar images after therapeutic dose I-131 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Many potential errors in radionuclide scintigraphy could occur and reporting should be done with caution [3] , [4] . Because of the harmful effects of radioiodine [8] , [9] , recognition of potential false-positive 131 I scintigraphy is critical to avoid renewal therapeutic doses of radioactive iodine.…”
Section: Discussionmentioning
confidence: 99%